Efektivitas Efektivitas Pembelajaran Tahfidz Al-Qur'an di SMPIT An-Naas Binjai - indriani ritonga; Nurhalima Tambunan (Al-Munawwarah : Jurnal Pendidikan Islam, 2022)
This study aims to see the effectiveness of learning tahfidz al-Qur'an at SMPIT An-Naas Binjai.